1994
DOI: 10.1002/j.1460-2075.1994.tb06428.x
|View full text |Cite
|
Sign up to set email alerts
|

Correction of xeroderma pigmentosum repair defect by basal transcription factor BTF2 (TFIIH).

Abstract: ERCC3 was initially identified as a gene correcting the nucleotide excision repair (NER) defect of xeroderma pigmentosum complementation group B (XP‐B). The recent finding that its gene product is identical to the p89 subunit of basal transcription factor BTF2(TFIIH), opened the possibility that it is not directly involved in NER but that it regulates the transcription of one or more NER genes. Using an in vivo microinjection repair assay and an in vitro NER system based on cell‐free extracts we demonstrate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
82
0
2

Year Published

1994
1994
2005
2005

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(86 citation statements)
references
References 57 publications
2
82
0
2
Order By: Relevance
“…By implication, the human genes that encode p62 protein (the Tfb1 homolog) and p44 protein (the Ssl1 homolog) are likely also required for NER. Immunodepletion studies with antibodies against p62 and p44 proteins inhibit in vitro NER in human cell extracts (13,25). However, the entire TFIIH complex was also depleted from the extracts in these studies.…”
Section: Fig 5 Complementation Of Ner Inmentioning
confidence: 80%
See 2 more Smart Citations
“…By implication, the human genes that encode p62 protein (the Tfb1 homolog) and p44 protein (the Ssl1 homolog) are likely also required for NER. Immunodepletion studies with antibodies against p62 and p44 proteins inhibit in vitro NER in human cell extracts (13,25). However, the entire TFIIH complex was also depleted from the extracts in these studies.…”
Section: Fig 5 Complementation Of Ner Inmentioning
confidence: 80%
“…Core TFIIH-Ssl2 is required for both transcription by RNA polymerase II and nucleotide excision repair (NER) in S. cerevisiae and humans (4,23,25,28). Consistent with their requirement for transcription, SSL2, RAD3, TFB1, and SSL1 are essential yeast genes (10-12, 17, 18, 34).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These findings were mainly derived from either the use of a microinjection approach or the use of DNA damaging agents that induce p53-mediated apoptosis. Microinjection techniques have been used extensively by us and other laboratories to study biological functions in primary cells (Weeda et al, 1990;van Vuuren et al, 1994;Attardi et al, 1996;Wang et al, 1996Wang et al, , 2001van Gool et al, 1997;Spillare et al, 1999;Winkler et al, 2000). As the SV-40T antigen can bind to and inactivate p53, our studies require the use of primary cells instead of SV-40 immortalized cells.…”
mentioning
confidence: 99%
“…Five of the subunits of the mammalian core TFIIH factor, p89/XPB/ERCC3 (Schae er et al, 1993), XPD/ERCC2 , p62 , p34 and p44 , have been implicated in DNA excision repair activity as well as in transcription. It has been demonstrated that p53 binds to p62 (Xiao et al, 1994), p89/XPB/ERCC3 (Wang et al, 1994) and XPD/ERCC2 , components of the basal transcription and nucleotide excision repair factor TFIIH/BTF2 (Schae er et al, 1993;van Vuuren et al, 1994).…”
Section: Introductionmentioning
confidence: 99%